Diversification And Firm Value: Analysing The Role Of Managerial Ability, Corporate Governance And Ceo Characteristics - Lee, Chyn Hwa (2023)
Diversification is a hugely popular growth strategy among Malaysian firms. However, in light of the diversification discount and subsequent refocusing efforts of Western firms in recent decades, it is essential to re-examine whether diversification creates value for firms critically. Addressing the diversification premium/discount conundrum, this study explores whether managerial ability influences the relationship between diversification and firm value. In addition, this study examines CEO personal attributes that are compatible with diversified firms, an aim motivated by the upper echelon theory. Furthermore, agency theory demonstrates that managers have the tendency to be involved in agency issues. Thus, this study investigates whether the moderating effect of managerial ability on the relationship between diversification and firm value will be further enhanced when firms have good corporate governance. The sample data includes all KLSE-listed firms across nine sectors: consumer products, construction, industrial products, technology, IPC, hotel, plantation, properties, as well as trading and services. Nine years (2009 to 2017) of firm annual data were collected from the Datastream/Worldscope database. Information on CEO attributes (age and education) and corporate governance (ratio of independent director and duality) was manually collected from annual reports.